Barrès contre Ruskin - Jessica Desclaux (Cahiers Victoriens et Edouardiens)
In many aspects Maurice Barrès (1862–1923) could have been a fervent disciple of Ruskin: an art lover influenced by the London aesthetes, a great reader of Rio’s work, On Christian Art, a writer on Venice, a political figure who came to adhere to traditionalism, a defender of the churches of France, one of the creators of the 1913 law on national heritage. However Barrès resisted Ruskin’s ideas, due to his interest in the Italian Renaissance, to his greater affinity with the tastes and sensibility of Walter Pater and of Stendhal, and also maybe as a reaction to fashion, as his satire of Ruskin’s pilgrims shows. To respond to Ruskin, he didn’t write a theoretical essay on art, but he inserted in novel or travel writing short polemical meditations. They testified to his increasing first-hand knowledge of Ruskin’s writings and they mostly dealt with the role the Italian Renaissance should play and with the representation of Venice. Barrès thus had a paradoxical role in the circulation of Ruskin’s ideas in France: he contributed to his fame—he is one of the first among few writers who used his name in a novel and, in 1904 he strongly advised Proust to translate St Mark’s Rest—, yet he also became an example of resistance to Ruskin. His followers, Rebell, Daudet, and Vaudoyer illustrated the way Barrès became a leader of this resistance, or at least helped to justify the anti-Ruskinian reaction in France.